Bacterial expression of larval peritrophins of Chryosomya bezziana - Wijffels, Gene; Voucoloco, Tony; Muharsini, Sri; Supriyanti, Florentina (Indonesian Animal Sciences Society, 2000)
Three candidate antigens, Chrysomya bezziana peritrophin-48, Chrysomya bezziana peritrophin-15 and Chrysomya bezziana peritrophin-42, were prepared for recombinant protein production in Escherichia coli using a variety of expression vectors. Cb peritrophin-48 was expressed as a recombinant protein possessing a carboxy-terminal hexaHis tag. Cb peritrophin-15 was expressed as both a glutathione S-transferase fusion protein and as an amino-terminal hexaHis tagged protein. The glutathione Stransferase Cb peritrophin-15 construct produced a heterogeneous group of fusion proteins. Cb peritrophin-42 was also expressed as an amino-terminal hexaHis tagged protein. The two putative domains of Cb peritrophin-42 were also separately expressed, again with amino-terminal hexaHis tags. Cultures of the hexaHis constructs Cb peritrophin-48, -15 and â42 were demonstrated to be useful for the production and purification of these protein antigens and were scaled-up for vaccine trials and protein characterization studies. Â Key words: Chrysomya, peritrophic membrane, peritrophin, recombinant protein, hexaHis tag, GST